2000
DOI: 10.1590/s0103-84782000000100005
|View full text |Cite
|
Sign up to set email alerts
|

Correlações canônicas: II - análise do rendimento de grãos de feijão e seus componentes

Abstract: Trinta e dois genótipos de feijão (Phaseolus vulgaris L.) foram avaliados em Lages/SC, em sete caracteres de importância agronômica e da produção de grãos por unidade de área. O experimento, em blocos casualizados com quatro repetições, foi conduzido no período de "safrinha", no ano agrícola de 1995/96. Este trabalho teve como objetivo estimar a intensidade de associação entre os grupos primários e secundários responsáveis pelo rendimento de grãos. O primeiro grupo de variáveis (primários) foi constituído pelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 3 publications
0
17
0
4
Order By: Relevance
“…It seems that the estimates obtained by the path analysis varied in function of genotypes, locations, years and sowing seasons, which would explain the variations in magnitude, sign and order of importance found in the literature (Santos and Vencovsky, 1986;Nienhuis and Singh, 1986;Peternelli et al, 1994;Coimbra et al, 1998aCoimbra et al, , 1998bCoimbra et al, , 1998cCoimbra et al, , 1999bCoimbra et al, , 1999cCoimbra et al, , 2000Kurek et al, 2001;Ribeiro et al, 2001aRibeiro et al, , 2001bCoelho et al, 2002;Furtado et al, 2002).…”
Section: Resultsmentioning
confidence: 96%
“…It seems that the estimates obtained by the path analysis varied in function of genotypes, locations, years and sowing seasons, which would explain the variations in magnitude, sign and order of importance found in the literature (Santos and Vencovsky, 1986;Nienhuis and Singh, 1986;Peternelli et al, 1994;Coimbra et al, 1998aCoimbra et al, , 1998bCoimbra et al, , 1998cCoimbra et al, , 1999bCoimbra et al, , 1999cCoimbra et al, , 2000Kurek et al, 2001;Ribeiro et al, 2001aRibeiro et al, , 2001bCoelho et al, 2002;Furtado et al, 2002).…”
Section: Resultsmentioning
confidence: 96%
“…Genetic correlation is the party of the heritability that may be caused pleiotropic effects or linked genes (Coimbra et al, 2000). The genetic correlation between leaf length and 100-grain weight traits was 0.58; between leaf length and pod length traits it was 0.54; between pod length and 100-grain weight, it was 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…Research performed by Coimbra et al (2000) found high and positive correlation coefficient between the number of pods per plant and grain yield. The NP I G for IGH in Tenente Portela-RS revealed direct effects with null coefficients.…”
Section: Direct and Indirect Effects Between Traitsmentioning
confidence: 97%